Donor‐specific chimeric antigen receptor Tregs limit rejection in naive but not sensitized allograft recipients. Issue 6 (11th February 2020) - Sicard, Antoine; Lamarche, Caroline; Speck, Madeleine; Wong, May; Rosado‐Sánchez, Isaac; Blois, Mathilde; Glaichenhaus, Nicolas; Mojibian, Majid; Levings, Megan K.
Abstract : Cell therapy with autologous donor‐specific regulatory T cells (Tregs) is a promising strategy to minimize immunosuppression in transplant recipients. Chimeric antigen receptor (CAR) technology has recently been used successfully to generate donor‐specific Tregs and overcome the limitations of enrichment protocols based on repetitive stimulations with alloantigens. However, the ability of CAR‐Treg therapy to control alloreactivity in immunocompetent recipients is unknown. We first analyzed the effect of donor‐specific CAR Tregs on alloreactivity in naive, immunocompetent mice receiving skin allografts. Tregs expressing an irrelevant or anti‐HLA‐A2‐specific CAR were administered to Bl/6 mice at the time of transplanting an HLA‐A2 + Bl/6 skin graft. Donor‐specific CAR‐Tregs, but not irrelevant‐CAR Tregs, significantly delayed skin rejection and diminished donor‐specific antibodies (DSAs) and frequencies of DSA‐secreting B cells. Donor‐specific CAR‐Treg–treated mice also had a weaker recall DSA response, but normal responses to an irrelevant antigen, demonstrating antigen‐specific suppression. When donor‐specific CAR Tregs were tested in HLA‐A2‐sensitized mice, they were unable to delay allograft rejection or diminish DSAs. The finding that donor‐specific CAR‐Tregs restrain de novo but not memory alloreactivity has important implications for their use as an adoptive cell therapy in transplantation. Abstract : Donor‐specific, chimeric antigen receptor regulatory T cells can diminish skin graft rejection and humoral alloreactivity in naïve but not sensitized immunocompetent mice.